Screen saver will aid search for cancer cure. - Johnston, Chris (Times Higher Education Supplement, 2001)
Reports on the Oxford University's project which will enable computer users to download a screensaver-like software that will harness unused computer processing power to screen molecule packages that could become cancer drugs. Duration of the downloading process; Estimated number of molecules to be screened in a bid to develop effective treatments for cancer.